Adalimumab alone and in combination with disease-modifying antirheumatic drugs for the treatment of rheumatoid arthritis in clinical practice: the Research in Active Rheumatoid Arthritis (ReAct) trial. Issue 6 (28th February 2007) - Burmester, Gerd R; Mariette, Xavier; Montecucco, Carlomaurizio; Monteagudo-Sáez, Indalecio; Malaise, Michel; Tzioufas, Athanasios G; Bijlsma, Johannes W J; Unnebrink, Kristina; Kary, Sonja; Kupper, Hartmut
Abstract : Objective: To evaluate the safety and effectiveness of adalimumab alone or in combination with standard disease-modifying antirheumatic drugs (DMARDs) for the treatment of rheumatoid arthritis (RA). Methods: Patients with active RA despite treatment with DMARDs or prior treatment with a tumour necrosis factor antagonist participated in a multicentre, open-label clinical study of adalimumab 40 mg every other week for 12 weeks with an optional extension phase. Patients were allowed to continue with pre-existing traditional DMARDs. Long-term safety results are reported for all patients (4210 patient-years (PYs) of adalimumab exposure). The observed effectiveness results at week 12 are reported using American College of Rheumatology (ACR) and European League Against Rheumatism (EULAR) response criteria. Results: Among the 6610 treated patients, adalimumab was generally well tolerated. Serious infections occurred in 3.1% of patients (5.5/100 PYs, including active tuberculosis, 0.5/100 PYs). Demyelinating disease (0.06%) and systemic lupus erythematosus (0.03%) were rare serious adverse events. The standardised incidence ratio of malignancy was 0.71 (95% CI 0.49 to 1.01). The standardised mortality ratio was 1.07 (95% CI 0.75 to 1.49). At week 12, 69% of patients achieved an ACR20 response, 83% a moderate, and 33% a good EULAR response. Adalimumab was effective in combination with a variety of DMARDs. The addition of adalimumab to antimalarials was comparably effective to the combination of adalimumab and methotrexate. Conclusions: Considering the limitations of an open-label study, adalimumab alone or in combination with standard DMARDs appeared to be well tolerated and effective in 6610 difficult-to-treat patients with active RA treated in clinical practice.